(3EQTGO GdYbd GdSdje Edi eRGjG GdcJGH GdcQjes - (3GdYeGOj, nCoHh GdoqSoYhO, eMeO Hf eMeO Hf eUWai, J (B982(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; SHMGf ef CQSd QShdg HGdgOi hOjf GdMb hHjf dg ef TYGFQ GdTQGFY ajbhd GdYHO GdabjQ CHh GdSYhO Hf eMeO GdYeGOj Ef GdZGjI GdbUhi ef JMQjQ fSNI GdYGde heG cGf MQa efg eSWhQG djSJ EdG eYQaI GdUGfY GdeLjO hYHGOI GdHGQF GdeYjO fGhjG Cf CSejg YfO JeGeg HJhajb Gddg JYGdi hEfYGeg EQTGO GdYbd GdSdje Edi eRGjG GdcJGH GdcQjes
(3BNQgG (B:s
( (3dbhe jDefhf (B) : (3Cj jUObhfg dCfge GdefJaYhf Hg hCeG ef YOGge adG jgJOhf HgOGg hdG jfJaYhf HLOhGg Yf QShd Gddg Udi Gddg Ydjg hSde (B: " (3YdehG CQbGce ShQI jhSa aEfg CjeG eSde JdGgG hYdegG Cgdg heG edcJ jejfg ghf Gddg Ydjg ScQGJ GdehJ hCYWGg GdbhI Cf dG jMSO eSdeG (B"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 59s
(3eYLe GdeDdajf (B3 / 693s
(3cTa GdXfhf (B1 / 65s
(3TPQGJ GdPgH (B8 / 398s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs